2017
DOI: 10.5740/jaoacint.17-0056
|View full text |Cite
|
Sign up to set email alerts
|

Screening Natural Content of Water-Soluble B Vitamins in Fish: Enzymatic Extraction, HILIC Separation, and Tandem Mass Spectrometric Determination

Abstract: Despite the potential of LC with tandem MS (MS/MS) in improving sensitivity and selectivity, analytical methods are scarce for the determination of protein-bound and phosphorylated forms of B vitamins in food. This prompted us to develop a method for LC-MS/MS determination of naturally occurring nicotinamide, nicotinic acid, thiamine, pyridoxine, riboflavin, pantothenic acid, biotin, folic acid, and cyanocobalamin in fish. Baseline separation of the vitamins was achieved in a hydrophilic interaction LC conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…This mainly due to the gradual release of B3 (nicotinic acid and nicotinamide) within the first four hours incubation (increased 17% to 54% comparing to those from 1 h incubation), and its significant loss during overnight incubation (reduced 69% to 98% comparing to those from 4 h incubation, Figure 1). Similar observation was reported by Chatterjee et al (2017), with a 4 h extraction approach resulting in a higher level of B3 (nicotinic acid and nicotinamide) in fish comparing to 18 h incubation. Note that since biotin (B8) or cyanocobalamin (B12) were not detected in lentil seeds, for samples containing these two B vitamins, the extraction condition may need to be optimized accordingly.…”
Section: Methods Development On B Vitamin Extractionsupporting
confidence: 88%
“…This mainly due to the gradual release of B3 (nicotinic acid and nicotinamide) within the first four hours incubation (increased 17% to 54% comparing to those from 1 h incubation), and its significant loss during overnight incubation (reduced 69% to 98% comparing to those from 4 h incubation, Figure 1). Similar observation was reported by Chatterjee et al (2017), with a 4 h extraction approach resulting in a higher level of B3 (nicotinic acid and nicotinamide) in fish comparing to 18 h incubation. Note that since biotin (B8) or cyanocobalamin (B12) were not detected in lentil seeds, for samples containing these two B vitamins, the extraction condition may need to be optimized accordingly.…”
Section: Methods Development On B Vitamin Extractionsupporting
confidence: 88%
“…Recoveries described in various foods [ 24 , 26 ], e.g., carrot [ 32 ], anchovy [ 32 ], garlic [ 32 ], chinoa [ 32 ], kiwi [ 43 ], tomato pulp [ 43 ], fish [ 66 ], cooked sausages [ 28 ], cow milk [ 23 , 55 , 68 ], Italian pasta [ 44 ], wheat [ 29 ], maize flour [ 43 ], and whole wheat flour [ 27 ], ranged between 15 and 118% depending on the matrix, extraction method, detection apparatus, and vitamer. Important factors when assessing the recoveries of B 6 molecules refer to the extraction procedure and sample workup, since incomplete extraction or dephosphorylation/deglycosylation by enzymes has a crucial impact on the method.…”
Section: Resultsmentioning
confidence: 99%
“…Inter- and intra-day precisions for foodstuff reported in the literature vary between 2 and 12 and between 1 and 5% depending on the matrix, vitamer, and method, respectively [ 23 , 24 , 26 , 28 , 43 , 58 , 66 , 68 ]. Hereby, Gentili et al reported inter-day precisions < 12% for B 6 vitamers in maize flour, while Kall et al noted an internal reproducibility of 5.6% for PN in Graham flour [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as highlighted by Fatima et al (2019) [36], a very limited number of validated methods utilising HILIC separation coupled to MS detection have been developed to analyse water soluble vitamins in complex food matrices. A study by Chatterjee et al (2017) [37] developed a LC-MS/MS method targeting nine water-soluble vitamins in fish using HILIC separation for increased sensitivity. The authors optimised an enzymatic hydrolysis method to subsequently extract B vitamins; including nicotinamide, nicotinic acid, pyridoxine, pantothenic acid, biotin, thiamine, riboflavin and cyanocobalamin from fish flesh.…”
Section: Introductionmentioning
confidence: 99%